Liability of financial supervisors and resolution authorities - Busch, Danny 1974-; Gortsos, Christos V.; McMeel, Gerard (Oxford University Press, 2022)
"This book offers a thorough overview, analysis and discussion of the liability regimes which apply to financial supervisors and resolution authorities at EU level, at the level of selected individual EU Member States and in major jurisdictions worldwide. It offers a unique and thorough access to a topic that is of great practical and theoretical importance. The book also contains a thorough comparative law evaluation"--